Anti-Pseudomonas aeruginosa activity of natural antimicrobial peptides when used alone or in combination with antibiotics - Chen, Xueqi; Su, Shan; Yan, Yan; Yin, Limei; Liu, Lihong (Frontiers in Microbiology, 2023)
The World Health Organization has recently published a list of 12 drug-resistant bacteria that posed a significant threat to human health, and Pseudomonas aeruginosa (P. aeruginosa) was among them. In China, P. aeruginosa is a common pathogen in hospital acquired pneumonia, accounting for 16.9-22.0%. It is a ubiquitous opportunistic pathogen that can infect individuals with weakened immune systems, leading to hospital-acquired acute and systemic infections. The excessive use of antibiotics has led to the development of various mechanisms in P. aeruginosa to resist conventional drugs. Thus, there is an emergence of multidrug-resistant strains, posing a major challenge to conventional antibiotics and therapeutic approaches. Antimicrobial peptides are an integral component of host defense and have been found in many living organisms. Most antimicrobial peptides are characterized by negligible host toxicity and low resistance rates, making them become promising for use as antimicrobial products. This review particularly focuses on summarizing the inhibitory activity of natural antimicrobial peptides against P. aeruginosa planktonic cells and biofilms, as well as the drug interactions when these peptides used in combination with conventional antibiotics. Moreover, the underlying mechanism of these antimicrobial peptides against P. aeruginosa strains was mainly related to destroy the membrane structure through interacting with LPS or increasing ROS levels, or targeting cellular components, leaded to cell lysis. Hopefully, this analysis will provide valuable experimental data on developing novel compounds to combat P. aeruginosa.